2014
DOI: 10.1097/mib.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile and Pediatric Inflammatory Bowel Disease

Abstract: In conclusion, this study demonstrates that pediatric IBD is associated with increased C. difficile detection. Patients with C. difficile tend to have active colonic disease and a more severe disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…In adult outpatients with ileal-anal pouch anastomosis (IPAA) for IBD, incidence of CDI is 10.7%-18.3%[33,34]. The incidence of CDI in IBD among pediatric patients is 7.8%-69%, similarly with a higher incidence among patients with UC as opposed to CD[35-40]. …”
Section: Discussionmentioning
confidence: 99%
“…In adult outpatients with ileal-anal pouch anastomosis (IPAA) for IBD, incidence of CDI is 10.7%-18.3%[33,34]. The incidence of CDI in IBD among pediatric patients is 7.8%-69%, similarly with a higher incidence among patients with UC as opposed to CD[35-40]. …”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts with data in patients with IBD, who are less likely to have been exposed to antibiotics than controls with C. difficile infection. 11,27 Gut microbiota composition differs in patients with CeD compared with healthy controls, with an increase of certain Clostridia species. 16,28,29 One possible explanation for the increased risk of C. difficile infection among patients with CeD relates to the treatment with a gluten-free diet.…”
Section: Discussionmentioning
confidence: 99%
“…31 One previous study found that children with inflammatory bowel disease had carriage rates of C. difficile nearly 10 times greater than those of children with CeD, though in that study those with inflammatory bowel disease included inpatients (which likely included patients in the midst of a disease flare) while those with CeD were restricted to outpatients. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 22 Similar results were also seen in children in a prospective multicenter study with detection of C. difficile toxins A and B by enzyme immunoassay giving a 10-fold higher detection in children with IBD compared with children with celiac disease (7.5% versus 0.8%; P = 0.008); this study however included both symptomatic and asymptomatic subjects. 23 Interestingly, a further study did not find a significant difference in the prevalence of toxigenic C. difficile between pediatric patients with IBD and controls using PCR to detect the toxin B gene (C. difficile detection of 11.6% in patients with Crohn's disease, 18.4% in patients with ulcerative colitis [UC], and 11.8% in controls [ P = 0.25]); however, this study looked at both inpatients and outpatients, and also likely symptomatic and asymptomatic colonization because some patients who tested positive also had diarrhea. 24 Furthermore, as compared with enzyme-linked immunoassay testing, PCR testing for detection of the toxin B gene of C. difficile is significantly more sensitive.…”
Section: Colonizationmentioning
confidence: 99%
“… 30 In pediatric IBD, antibiotic exposure has not been found to be the major risk factor for CDAD or C. difficile colonization. 18 , 23 Instead, it is proposed that the underlying dysbiosis with decreased diversity of species that is found in IBD, in both Crohn's disease and UC, predisposes to the loss of colonization resistance to C. difficile in IBD, leading to increased rates of CDI in this population. 31 , 32 Moreover, increased Proteobacteria and decreased Bacteroidetes have also been reported in those with IBD compared with non-IBD controls, 32 similar to some reports of microbiome changes in recurrent CDI.…”
Section: Pathogenesismentioning
confidence: 99%